2021
DOI: 10.1186/s13148-021-01119-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel DNA methylation signature is associated with androgen receptor activity and patient prognosis in bone metastatic prostate cancer

Abstract: Background Patients with metastatic prostate cancer (PC) are treated with androgen deprivation therapy (ADT) that initially reduces metastasis growth, but after some time lethal castration-resistant PC (CRPC) develops. A better understanding of the tumor biology in bone metastases is needed to guide further treatment developments. Subgroups of PC bone metastases based on transcriptome profiling have been previously identified by our research team, and specifically, heterogeneities related to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…With the rapid development of genomics, a large number of genomic data were obtained from the microarray chip and high-throughput sequencing, which helped us to better understand the tumor heterogeneity and guide future clinical decision-making ( Miyamoto et al, 2018 ; Labrecque et al, 2019 ; Puhr et al, 2021 ; Ylitalo et al, 2021 ). For example, the SPP1 gene was identified as an extracellular matrix signature, which was remarkably up-regulated in mCRPC and may be a novel therapeutic target for mCRPC patients ( Pang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of genomics, a large number of genomic data were obtained from the microarray chip and high-throughput sequencing, which helped us to better understand the tumor heterogeneity and guide future clinical decision-making ( Miyamoto et al, 2018 ; Labrecque et al, 2019 ; Puhr et al, 2021 ; Ylitalo et al, 2021 ). For example, the SPP1 gene was identified as an extracellular matrix signature, which was remarkably up-regulated in mCRPC and may be a novel therapeutic target for mCRPC patients ( Pang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The duration of the initially favorable response is highly variable between patients. We have shown that human PC bone metastases can be separated into different subgroups with different transcriptome, proteome, metabolome, genetics, epigenetics, immune phenotypes, clinical behavior, and response to standard treatments [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Or in other words, there are different types of aggressive PC.…”
Section: Introductionmentioning
confidence: 99%
“…The dataset GSE173330 supplied DNA methylation data from several tissues in toothed whales ( N = 254) and dolphin ( N = 291) ( Robeck et al, 2021 ). The last dataset GSE174613 analyzed samples of non-malignancy obtained from prostatectomy specimens ( n = 12) and of bone metastasis tissue samples obtained from separate prostate cancer patients ( n = 70) ( Ylitalo et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%